Vaccine use in Canadian cow-calf herds and opportunities for improvement - Lazurko, Madelana M.; Erickson, Nathan E.N.; Campbell, John R.; Gow, Sheryl; Waldner, Cheryl L. (Frontiers in Veterinary Science, 2023)
Vaccinations are one of the most impactful tools available to cow-calf producers to control within herd disease and later, in feedlots. While vaccine use has been studied across Canada, inconsistent and variable regional data makes analysis and interpretation difficult. The objective of this study was to describe vaccination protocols and factors associated with vaccine use in Canadian cow-calf herds and define associations between vaccine use and productivity outcomes. Surveys describing vaccine use in 2020 were collected from 131 cow-calf herds (40 eastern, 91 western), recruited through a national beef cattle surveillance program. Ninety-two percent of cows and replacement heifers, and 72% of bulls were vaccinated with Infectious Bovine Rhinotracheitis (IBR), Bovine Viral Diarrhea Virus (BVDV), Parainfluenza3 Virus (PI3), and Bovine Respiratory Syncytial Virus (BRSV). At least half of cows and bulls were vaccinated for clostridial pathogens and cows and heifers for viral calf scours. Clostridial vaccines were significantly more likely to be used in western Canada compared to eastern Canada. While 92% of producers vaccinated suckling calves against IBR/BRSV/PI3, only 47% provided a second vaccine prior to weaning; 78% of calves were also vaccinated at least once for BVDV before weaning. Producers who vaccinated calves against IBR/BRSV/PI3 before 3 months of age provided a second dose prior to weaning more often than producers who administer the first IBR/BRSV/PI3 vaccine later. Vaccine use has increased across Canada, particularly in calves, prior to weaning. Relative to label recommendations for annual vaccination, clostridial vaccines were generally underutilized in cows and bulls, and by producers in eastern Canada as compared to western Canada. Opportunities also exist to improve adherence to label recommendations for the booster dose of scours vaccine when used in bred replacement heifers. Protocols including product choices, the timing and boosting of respiratory vaccines in nursing calves vary widely across herds. Use of intranasal vaccines in neonatal calves less than two weeks old has increased in western Canada compared to previous reports. There is a need to better understand how timing of vaccination in nursing calves contributes to effectiveness, for respiratory disease in nursing and weaned calves.